Impact of Interactions Between Zn(II) and Selenites in an Aquatic Environment on the Accumulation of Se and Zn in a Fungal Cell - Małgorzata Kałucka; Piotr Podsadni; Agnieszka Szczepańska; Eliza Malinowska; Anna Błażewicz; Jadwiga Turło (Molecules)
Our attempts to obtain a new mushroom-derived immunostimulatory preparation containing organically bound selenium and zinc have focused on the interactions between selenites and zinc(II) in liquid culture media and their effects on transport into the mushroom cell. Previously, we found that, even if Zn2+ and SeO32− concentrations in the liquid medium are not high enough to precipitate ZnSeO3, the accumulation of selenium in the presence of zinc, and zinc in the presence of selenites, significantly dropped. This effect was more dependent on the molar ratio of ions in the medium than on the concentration values. We hypothesized that the formation of zinc–selenite soluble complexes with charges depending on the ion concentration ratio in the aquatic environment affects the first stage of ion transport into the fungal cell—biosorption. To verify this, we found the zinc–selenite molar ratio at which the complexes of the highest stability are formed, examined the influence of the molar ratio of ions in the medium on the concentration of Zn and Se in the mushroom cell wall, and investigated the correlation between the concentration of selenites not bound in complex compounds and the Se concentration in the cell wall. The results indicate that the molar fraction of Zn(II) in a liquid medium in the range of 0.5–0.6 promotes the formation of the most stable complexes. At the same time, it significantly reduces the percentage of free selenites in the medium and most strongly inhibits the biosorption process of both zinc and selenium.